UAV Orthophoto poster Alor Setar, Kedah - Abdullah, Alias; Ibrahim, Illyani; Ibrahim, Mansor; Hj. Mohd. Noor, Norzailawati; Harun, Nor Zalina; Abdul Latip, Nurul Syala; Abdullah, Ahmad Afiq Aiman; N Murtaza, Fatin Farhana
UAV Orthophoto of Alor Setar city with scale 1:27000